The Influence Of Financial Literacy, Lifestyle, Use Of M-Banking With A Utaut2 Approach On Financial Behavior - Elsa Mayangsari; Heni Safitri; Dedi Hariyanto (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research aims to determine whether there is a connection between M-Banking usage, lifestyle factors, and financial literacy. With a positive data collection strategy and a sample size of 150 participants, this research applies an associative methodology. Participants must be Singkawang City residents, aged 17–50, and M-Banking app users in order to be considered for the study. Statistical methods are employed in the analysis, including the following: multiple linear regression, correlation and determination coefficient, simultaneous testing (F test), and partial testing (t test). The data is linear, has a normal distribution, and does not show signs of multicollinearity; these findings are confirmed by the standard assumption test. The variables are strongly associated with one another, as shown by the correlation value of 0.523. According to the coefficient of determination (R2), the variables that were included in this research accounted for 28% of the variance in financial behavior, while other unexplained factors influenced the remaining 72%. Preliminary research shows that financial literacy and M-Banking use significantly affect financial behavior for the better. In contrast, lifestyle has a positive effect but is not statistically significant in influencing financial behavior.